Overexpression of Pyrus sinkiangensis HAT5 enhances drought and salt tolerance, and low-temperature sensitivity in transgenic tomato - Liu, Xiaoyan; Li, Aowei; Wang, Saisai; Lan, Chengfang; Wang, Yize; Li, Jin; Zhu, Jianbo (Frontiers in Plant Science, 2022)
The homeodomain-leucine zipper protein HAT belongs to the homeodomain leucine zipper subfamily (HD-Zip) and is important for regulating plant growth and development and stress tolerance. To investigate the role of HAT5 in tolerance to drought, salt, and low temperature stress, we selected a HAT gene from Pyrus sinkiangensis Yü (Pyrus sinkiangensis T.T. Yu). The sequences were analyzed using ioinformatics, and the overexpressed tomato lines were obtained using molecular biology techniques. The phenotypes, physiological, and biochemical indexes of the wild-type and transgenic tomato lines were observed under different stress conditions. We found that the gene had the highest homology with PbrHAT5. Under drought and NaCl stress, osmotic regulatory substances (especially proline) were significantly accumulated, and antioxidant enzyme activities were enhanced. The malondialdehyde level and relative electrical conductivity of transgenic tomatoes under low temperature (freezing) stress were significantly higher than those of wild-type tomatoes. The reactive oxygen species scavenging system was unbalanced. This study found that PsHAT5 improved the tolerance of tomatoes to drought and salt stress by regulating proline metabolism and oxidative stress ability, reducing the production of reactive oxygen species, and maintaining normal cell metabolism. In conclusion, the PsHAT5 transcription factor has great potential in crop resistance breeding, which lays a theoretical foundation for future excavation of effective resistance genes of the HD-Zip family and experimental field studies.